Efficacy and Tolerability of Travoprost 0.004%/Timolol 0.5% Fixed-Dose Combination for the Treatment of Primary Open-Angle Glaucoma or Ocular Hypertension Inadequately Controlled with Beta-Blocker Monotherapy - Simon Fabian Lerner; Ki Ho Park; Douglas A. Hubatsch; Valeriy Erichev; Jose A. Paczka; Timothy V. Roberts (Journal of Ophthalmology)
Objective. To evaluate the efficacy and tolerability of travoprost 0.004%/timolol 0.5% fixed-dose combination (TTFC) in patients with open-angle glaucoma (OAG) or ocular hypertension (OHT) inadequately controlled on beta-blocker monotherapy. Methods. In this phase IV, open-label study, 156 patients on beta-blocker monotherapy with mean intraocular pressure (IOP) between 18 and 32 mmHg were randomized (no washout period) to receive TTFC for 8 weeks (TTFC group) or to continue beta-blocker monotherapy for 4 weeks followed by TTFC for the remaining 4 weeks (beta-blocker group). Results. The mean IOP (±standard deviation) at baseline in the TTFC and beta-blocker groups was 22.5±2.5 mmHg and 22.2±2.3 mmHg, respectively, and at weeks 4 and 8, was 16.7±3.1 mmHg and 16.1±3.1 mmHg, respectively, in TTFC group and 21.1±3.1 mmHg and 16.1±2.8 mmHg, respectively, in the beta-blocker group. There was a significant least squares mean difference between TTFC and beta-blocker in 8 a.m. IOP at week 4 (−4.6 mmHg; one-sided 95% confidence interval [−inf, −3.9]; p<0.0001 [primary endpoint]); the upper bound of the 95% confidence interval was within the prespecified limit (<0). Both treatments were well tolerated. Conclusion. Superior IOP control was achieved with TTFC in patients with OAG or OHT previously uncontrolled with beta-blockers. No new safety findings were identified. This trial is registered with ClinicalTrials.gov NCT02003391.